2021
DOI: 10.3390/ma14175016
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Mild Steel and 304 Stainless Steel in 1 M Hydrochloric Acid Solution by Tea Tree Extract and Its Main Constituents

Abstract: Tea tree extract, containing antioxidant constituents α-terpineol, terpinen-4-ol, and α-terpinene, has a wide range of applications in the cosmetic, food, and pharmaceutical industries. In this study, tea tree extract showed an anticorrosive effect under 1 M HCl solution on mild steel (MS) and 304 stainless steel (STS). Uniform corrosion for MS and pitting corrosion for STS at 298 K were retarded, with inhibition efficiencies of 77% and 86%, respectively. The inhibition of uniform and pitting corrosion was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…The corrosion inhibition efficiency of steel by Harmal roots, leaves, and flower extracts in sulfuric acid media was compared with other ones reported in the literature, Table 11 . The results showed that the three Harmal extracts studied at a low concentration of 83 ppm with high IE % (93%), averaged from the three extracts, are more effective towards the inhibition of C-steel corrosion compared to other reported ones: Date palm seed (2000 ppm, 91%) [ 58 ], tea tree (2250 ppm, 78.6%) [ 59 ], Ginkgo leaf extract (200 ppm, 90.0%) [ 60 ], and Brassica oleracea L (300 ppm, 92.7%) [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The corrosion inhibition efficiency of steel by Harmal roots, leaves, and flower extracts in sulfuric acid media was compared with other ones reported in the literature, Table 11 . The results showed that the three Harmal extracts studied at a low concentration of 83 ppm with high IE % (93%), averaged from the three extracts, are more effective towards the inhibition of C-steel corrosion compared to other reported ones: Date palm seed (2000 ppm, 91%) [ 58 ], tea tree (2250 ppm, 78.6%) [ 59 ], Ginkgo leaf extract (200 ppm, 90.0%) [ 60 ], and Brassica oleracea L (300 ppm, 92.7%) [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Undealloyed α-TPN@ Ag 55 Al 45 did not exhibit effective SERS enhancement, hence a characteristic peak around 3600 cm −1 for the line V was not observed. However, a small amount of α-TPN on the surface could still be proved due to the peak caused by the C-H stretching vibrations at around 2800-3000 cm −1 [42]. On the other hand, a weak peak at 3594 cm −1 corresponding to the O-H stretching was found in line VI samples and some peaks were at around 2800-3000 cm −1 .…”
Section: Surface Analysis and Characteristics Of Nps Pretreated With ...mentioning
confidence: 91%
“…A standard solution of NaOH at 1.0 mol/L was used to titrate the authigenic acid mixture with the addition of phenolphthalein, and the change in H + concentration in the authigenic acid system with time was calculated by the consumption of lye. The formula for calculating H + is shown in eq . , C acid = C NaOH × V t V acid where C acid is the H + concentration in the acid system, mol/L; C NaOH is the OH – concentration in the lye system, mol/L; V t is the volume of lye for titration, mL; and V acid is the acid volume, mL.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The formula for calculating H + is shown in eq 1 . 23 , 24 where C acid is the H + concentration in the acid system, mol/L; C NaOH is the OH – concentration in the lye system, mol/L; V t is the volume of lye for titration, mL; and V acid is the acid volume, mL.…”
Section: Materials and Methodsmentioning
confidence: 99%